Study on Cloud Based Integrated Bhulekh Model Transforming Revenue Administration and Digitally Empowering Society - Saurabh Gupta; Rajesh Kumar Gangal; Sameer Rajan (Research and Developments in Engineering Research Vol. 4, 2023)
The goal of the government is to deliver numerous citizen-centric services in a cost-effective and transparent manner. To do this, the government must leverage cutting-edge technology in novel ways and combine it with process reengineering models that include a range of stakeholders in service delivery. Additionally, the government can perform claim validation by directly verifying documentary proofs through created databases. The study highlights the remarkable initiative taken by the Government of Uttar Pradesh to transform Bhulekh 1.0 to Bhulekh 2.0, by employing cloud-based integration of stakeholders in revenue administration, including the registry office, revenue courts, banks, Aadhar, e-District, and Common Service Center (CSC). This transformation has set a new standard of digital delivery of services and improved the performance of Revenue Administration through MeghRaj Cloud. The cloud powered Bhulekh 2.0 is making significant progress towards creating a digitally empowered society by providing services from anywhere at any time in a responsive manner.